Bank Risk Taking Behaviour In Malaysia: Role Of Board And Ownership Structure - Loh, Linda; Chan , Sok Gee (Asian Academy of Management (AAM), 2017)
This paper examines the role of board structure and ownership concentration on bank risktaking of public listed commercial banks in Malaysia from 2001 to 2012. The study focuses on the bank-risk taking behaviour after the major bank consolidation in Malaysia in year 2000. Using two-market model to estimate the risk of the commercial banks in Malaysia, the results suggest that higher ownership concentration and larger board size resulted in higher bank risk-taking of the listed commercial banks in Malaysia. Given that the board structure is an important element of bank risk-taking, regulators should continue to enhance the monitoring of banks (where board size is large and ownership concentration is high) to control the banks’ potential for excessive risk taking